Accelerated start-up of a semi-commercial digester tank treating palm oil mill effluent with sludge seeding for methane production - Sulaiman, Alawi; Tabatabaei, Meisam; Mohd Yusoff, Mohd Zulkhairi; Ibrahim, Mohamad Faizal; Hassan, Mohd Ali; Shirai, Yoshihito (IDOSI Publications, 2010)
The modern closed digesters are becoming more popular for treating palm oil mill effluent (POME) and are currently being installed nationwide in Malaysia to replace the conventional open lagoons and tanks treatment system. This paper describes an accelerated start-up of the 500 m semi-commercial anaerobic digester 3 treating POME and methane gas recovery for clean development mechanism (CDM) project. Results showed that by direct seeding through the transfer of the sludge from either top or bottom of the open digester tank,the start-up period was significantly shortened. The bottom seed sludge transfer led to interesting results including a 24 day start-up period, stable pH condition (pH 6.8-7.2), high COD removal efficiency (>90%), satisfactory VFA to Alk ratio (<0.3), satisfactory biogas production of nearly 1.8 kg/m /d) and methane 3 composition of 50 to 60%. The presence of high amount of methanogens in the seed sludge significantly reduced the need for a long acclimatization period and the digester could be fed with POME within less than a day after the seed sludge transfer process was completed. Close examination using scanning electron microscopy (SEM) and fluorescence in situ hybridization (FISH) revealed abundant amount of bacteria and methanogens, in particular Methanosaeta sp., in the seed sludge samples, which are very important for successful acidogenesis and methanogenesis processes.